Capturing the cycle-scape in Chiang Mai: Realities and obstacles - Julian Huang (Faculty of Architecture, Chiang Mai University, 2020)
JED: Journal of Environmental Design is produced to disseminate the new and current state of knowledge in relation to research and design of architecture and environment. The journal first launched in 2014 and idexed in TCI tier 2 in 2017